Sequential activation of conventional and plasmacytoid dendritic cells in autoimmune pancreatitis and systemic lupus erythematosus: similarities and dissimilarities - Hara, Akane; Watanabe, Tomohiro; Minaga, Kosuke; Kamata, Ken; Strober, Warren; Kudo, Masatoshi (Frontiers in Immunology, 2025)
Type 1 autoimmune pancreatitis (AIP) and systemic lupus erythematosus (SLE) are caused by type I IFNs secreted by plasmacytoid dendritic cells (pDCs). Our understanding of the immune consequences before and after pDC activation in SLE is expanding, whereas knowledge on those in AIP are insufficient. In this article, we summarize the similarities and dissimilarities in pDC activation between AIP and SLE. In SLE, neutrophil extracellular traps containing self-DNA, anti-microbial peptides, and endogenous alarmins form anti-DNA antibody complexes, promoting type I IFN production by pDCs. Type I IFNs produced by pDCs function as initiators rather than effectors in SLE, as evidenced by the fact that these cytokines induce the maturation of conventional DCs (cDCs) leading to the expansion of autoreactive T cells and B cells. Notably, type I IFNs produced by pDCs were observed at the maturation phase but not at the induction phase in experimental AIP. Mechanistically, cDCs producing type I IFNs, C-X-C motif chemokine ligand 9 (CXCL9), and CXCL10 are initiator cells of AIP, and C-X-C chemokine receptor 3 (CXCR3)+T helper type 1(Th1) cells migrate to the pancreas in response to CXCL9 and CXCL10. CXCR3+Th1 cells produce C-C chemokine ligand 25 (CCL25) to attract C-C chemokine receptor 9 (CCR9)+pDCs to the pancreas. Pancreatic pDCs producing type I IFNs, CXCL9, CXCL10, and CXCR3+Th1 cells producing CCL25 form a positive feedback loop in which the sensing of intestinal dysbiosis induces large amounts of type I IFNs by pDCs.